A sociolingüística na (e da) alfabetização - Tarallo, Fernando (DELTA: Documentação e Estudos em Linguística Teórica e Aplicada, 2019)
This study is an overview of the influence of labovian sociolinguistic studies on literacy and the issues that literacy problems raise for sociolinguistics both in the States and in Brazil. As in this studies on linguistic variation, Labov and collaborators embark, since the sixties, on formal and functional hypotheses on literacy failure among blacks. Their conclusion is that, though there is an apparent increase in phonological and lexical acess of the dominant dialect by the minority group through schooling, the social and grammatical gap present signs of an increasing degree of seggregation. In the Brazilian context, two centers deserve mention: UFRJ and UFMG. The former, with its strict variationist approach, tries to check the inter-dialectal intelligibility between litterate and illiterate subjects, while the latter starts from "errors" in spelling, many of wich are given a sociolinguistic-variationist interpretation.